Diversity and health risk potentials of the Enterococcus population in tropical coastal water impacted by Hurricane Lane - Prakit Saingam; Doris Y. W. Di; Tao Yan (IWA Publishing, 2021)
Hurricane-caused stormwater runoffs transport diverse terrestrial pollutants, adversely impact microbiological water quality, and introduce fecal and other pathogens to coastal water environments. This study investigated the genotypic diversity, phylogenetic composition, antibiotic resistance patterns, and virulence gene repertoire of the Enterococcus population in the Hilo Bay coastal water after the immediate impact of Hurricane Lane. DNA fingerprinting of Enterococcus isolates exhibited large genotypic diversity, while 16S rRNA gene sequencing identified four major species, including E. faecalis (34.7%), E. faecium (22.4%), E. hirae (22.4%), and E. durans (18.4%). Four common enterococcal virulence genes (cylA, esp, asa1, and gelE) were detected in the Enterococcus population, with significant portions of E. durans (33.3%), E. faecalis (41.2%), E. faecium (36.4%), and E. hirae (27.3%) isolates possessing two or more virulence genes. Considerable antibiotic resistance to rifampin, erythromycin, tetracycline, and nitrofurantoin was detected in the Enterococcus population, with one E. durans isolate showing vancomycin resistance. The results indicate considerable health implications associated with Enterococcus spp. in the hurricane-impacted tropical coastal water, illustrating the needs for more comprehensive understanding of the microbiological risks associated with storm-impacted coastal water. HIGHLIGHTS The study investigated the Enterococcus population in a tropical coastal water immediately after the impact of a major hurricane.; Genotypic diversity and phylogenetic composition of the Enterococcus population were determined.; A significant portion of the Enterococcus population contains various virulence factors.; Considerable antibiotic resistance was detected in the Enterococcus population.;